Feasibility study of dissimilar joining of aluminum alloy 5052 to pure copper via thermo-compensated resistance spot welding. (15th September 2016) - Zhang, Yu; Li, Yang; Luo, Zhen; Yuan, Tao; Bi, Jing; Wang, Zheng Ming; Wang, Zhi Ping; Chao, Yuh Jin
Abstract: A parametric study was used to investigate the feasibility of dissimilar Al/Cu joining by a thermo-compensated resistance spot welding process. The tensile shear properties of the joints were found to be affected by both the weld's physical properties and metallurgical factors: (1) With increasing heat input, the nugget size and indentation increased, which led to the failure mode of the joint to change from interfacial failure to pull-out mode. (2) There was a critical heat input at which the microstructure changed in the fusion zone. At normal heat input, the fusion zone consisted of a significant amount of α-Al solid solution and a thin transition layer (α-Al/θ-CuAl2 eutectic to θ-CuAl2 ) at the Al/Cu interface, producing a high nugget's shear strength. At high heat input, the fusion zone mainly consisted of Al–Cu intermetallic compounds (IMCs), producing a low nugget's shear strength. The fractograph revealed cleavage features in the interfacial failure mode and dimples in the pull-out mode, which implied that the crack propagated respectively in the IMC zone and the periphery of the nugget. The Al/Cu thermo-compensated resistance spot weld joints presented a tensile shear peak load comparable to that of Al/Al joints, though their ductility was deteriorated by the IMCs. Graphical abstract: Highlights: Aluminum alloy and pure copper were successfully joined via thermo-compensated resistance spot welding. AISI 201 tape was put at Cu side to make sure work pieces could welded under resistance spot welding process. Scanning electron microscopy and X-ray diffractometry shows the microstructure was different under different parameters. The mechanical properties were affected by both weld's size and its microstructure. The Al/Cu thermo-compensated resistance spot welding joints possess comparable load bearing ability versus Al/Al joints.